Otherwise Known as Sheila the Great - Blume, Judy; Nang ChanYeema (New York, USA Puffin Books, 2003)
A summer in Tarrytown, NY is a lot of fun for ten-year-old Sheila even though her friends make her face up to some self-truths she doesn't want to admit.
Keywords: Adult Fiction